2017
DOI: 10.2196/jmir.7367
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Predicting Patterns of Early Response in a Web-Based Intervention for Depression

Abstract: BackgroundWeb-based interventions for individuals with depressive disorders have been a recent focus of research and may be an effective adjunct to face-to-face psychotherapy or pharmacological treatment.ObjectiveThe aim of our study was to examine the early change patterns in Web-based interventions to identify differential effects.MethodsWe applied piecewise growth mixture modeling (PGMM) to identify different latent classes of early change in individuals with mild-to-moderate depression (n=409) who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 56 publications
7
38
1
1
Order By: Relevance
“…Measures of psychological distress included the Outcomes Questionnaire (OQ‐45), and the Clinical Outcomes in Routine Evaluation (CORE). Only two studies used general psychological distress measures rather than disorder‐specific measures to assess symptom change (Lutz et al, ; Rubel et al, ), while two used a combination of both (Lutz, Stulz & Köck, ; Schibbye et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Measures of psychological distress included the Outcomes Questionnaire (OQ‐45), and the Clinical Outcomes in Routine Evaluation (CORE). Only two studies used general psychological distress measures rather than disorder‐specific measures to assess symptom change (Lutz et al, ; Rubel et al, ), while two used a combination of both (Lutz, Stulz & Köck, ; Schibbye et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous authors have suggested that the early response effect could be explained by a trend of improvement that began prior to the start of treatment, which might be indicative of regression to the mean (Beckham, ). Two of the reviewed studies did in fact observe that early pretreatment gains are associated with trajectories of improvement, however both studies still found significant effects of early response during treatment after controlling for pretreatment gains (Delgadillo et al, ; Lutz et al, ). On this basis, the effect of early response cannot be entirely explained by regression to the mean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes might be independent of usage duration. Behavioral pathways might also be important, though, as there is evidence that depressed individuals with more negative attitudes are more likely to discontinue the use of Internet interventions (Lutz et al, 2017). Regardless of the still unresolved question of how attitudes affect outcome among users of Internet interventions, the APOI might be used as a screening tool to identify individuals who may be well suited for these interventions, or to identify those who require support or for whom other interventions might be preferable.…”
Section: Discussionmentioning
confidence: 99%